Ten steps to identify atypical parkinsonism. Issue 12 (17th July 2006) - Abdo, W F; Borm, G F; Munneke, M; Verbeek, M M; Esselink, R A J; Bloem, B R
Abstract : Background: Balance impairment is a frequently encountered problem in patients with Parkinson's disease. A profound balance disorder, however, is an atypical feature. Methods: Tandem gait performance (10 consecutive tandem steps) was judged in 36 consecutive patients with Parkinson's disease and 49 consecutive patients with atypical parkinsonism. Results: Only 9 (18%) patients with atypical parkinsonism had a fully normal tandem gait (not a single side step) as opposed to 33 (92%) patients with Parkinson's disease. Analysis for the subgroup of patients with a disease duration of <3 years yielded the same diagnostic accuracy. Conclusions: Tandem gait performance has a good diagnostic ability to differentiate patients with atypical parkinsonism from those with Parkinson's disease, and might be used as an additional "red flag" to assist existing clinical tests in identifying atypical parkinsonism.